Pengaruh Pendidikan Kesehatan dengan Media Game Busar terhadap Pengetahuan Konsumsi Buah dan Sayur pada Murid Kelas 4 dan 5 di SDN 07 Pagi Kebayoran Lama Utara - Alfonsa Reni Oktavia; Falah Indriawati Barokah; irfan said; Dwi Ayu Lestari (Universitas Muhammadiyah Semarang, 2022)
Background: School-age children consume less fruit and vegetables than the recommended daily requirement. The low consumption of fruits and vegetables is due to the low level of nutritional knowledge. Lack of knowledge will reduce the ability to apply nutritional information, so that the consumption of healthy food will decrease and become a negative impact on the nutritional status of school-age children. Objective To determine the effect of health education with the Busar game media on knowledge of fruit and vegetable consumption in 4th and 5th grades students at Elementary Public School (SDN) 07 Pagi Kebayoran Lama Utara. Methods: Quantitative study using pre-experimental design with the type of one group pretest-posttest. The total population of this study was 128 students with a sample size of 56 students who were determined using the Slovin formula and selected by stratified random sampling. Bivariate data analysis was performed using the paired sample t-test. Results: A p value of 0.001 (≤0.05) was obtained which indicates that there is an impact of health education using the Busar game media on the level of knowledge of fruit and vegetable consumption. Conclusion: The busar game-based learning method is proven to be effective in increasing students' knowledge in understanding the importance of consuming vegetables and fruits.